Mini tuber production using yam (Dioscorea rotundata) vines - Shiwachi, H.; Kikuno, H.; Asiedu, Robert (Wiley, 2005)
Mini tubers were produced from two varieties of Dioscorea rotundata using vine cuttings planted in carbonized rice husk or coco-peat in a screen house. The cuttings established better and produced more mini tubers in carbonized rice husk than in coco-peat 100 days after planting. Vine cuttings of seven varieties planted in carbonized rice husk produced 1.7 ± 0.8 mini tubers per cutting with mean weight of 3.0 ± 2.7 g and 70.1% moisture content. About 63% of these sprouted after 77–105 days of storage under ambient air temperature. Vine cuttings of D. rotundata can be used to produce mini tubers within 100–120 days that could be used in germplasm exchange and for production of seed yams.